Factores Psicosociales Que Intervienen En El Rendimiento AcadÃ©mico Estudio De Caso: AnÃ¡lisis A Estudiantes De La Carrera De Cultura FÃsica Y Entrenamiento Deportivo - Sotomayor, CÃ©sar Mario RodrÃguez; MuÃ±oz, DarÃo Javier DÃaz; Rovayo, VÃctor Daniel Aldas; Moreno, Orlando David MazÃ³n; Bravo, HernÃ¡n Leopoldo Ponce (European Scientific Journal, ESJ, 2017)
The objective of the present research was to analyze the psychosocial factors that intervene in the academic performance of the students in the race of physical culture and sports training of the â€œUniversidad Nacional de Chimborazoâ€ in the academic period from September 2014 to February 2015. The study sample was 72 students of a population of 97 students, 57 male and 15 female. The methodology of this study uses a cross-sectional research, quasi-experimental, qualitative-quantitative, bibliographic, and field research. Based on the collection of data, the instruments used were the academic record. A questionnaire was developed which served to identify the psychosocial factors of the students. Among the most relevant results, it was evidenced that out of 97 students corresponding to 100%, only 25, that is 25.77%, exceeded the required score to approve the semester. Therefore, 72 students representing 74.22% obtained lower score than required for approval. In conclusion, it was obtained that the psychosocial factors that influenced the academic performance of the students were: the always consumption of cigarettes representing 25%. On the other hand, 55.56% had difficulty in sometimes distributing their time adequately for educational tasks.